Two Novel Mutations of ANKRD11 Gene and Wide Clinical Spectrum in KBG Syndrome: Case Reports and Literature Review - Kim, Su Jin; Yang, Aram; Park, Ji Sun; Kwon, Dae Gyu; Lee, Jeong-Seop; Kwon, Young Se; Lee, Ji Eun (Frontiers in Genetics, 2020)
Background KBG syndrome (OMIM #148050) is a rare, autosomal dominant inherited genetic disorder caused by heterozygous mutations in the ankyrin repeat domain-containing protein 11 (ANKRD11) gene or by microdeletion of chromosome 16q24.3. It is characterized by macrodontia of the upper central incisors, distinctive facial dysmorphism, short stature, vertebral abnormalities, hand anomaly including clinodactyly, and various degrees of developmental delay. KBG syndrome presents with variable clinical feature and severity among individuals. Here, we report two KBG patients who have different novel heterozygous mutations of ANKRD11 gene with wide range of clinical manifestations. Case Presentation Two novel heterozygous mutations of ANKRD11 gene were identified in two unrelated Korean patients with variable clinical presentations. The first patient presented with short stature and early puberty and was treated with growth hormone and gonadotropin-releasing hormone agonist without adverse effects. He had mild intellectual disability. In targeted exome sequencing, a novel de novo frameshift variant was identified in ANKRD11, c.5889del, and p. (Ile1963MetfsX9). The second patient had severe intellectual disability with epilepsy. He had normal height and prepubertal stage at the age of 11 years. He had psychopathological problems: autism spectrum disorder and overactive, stereotyped movement disorder. Whole exome sequencing was performed, and the novel heterozygous mutation, c3310dup, p. (Glu110GlyfsTer5) in ANKRD11 was identified. Conclusion KBG syndrome is often underdiagnosed because of its nonspecific features and phenotypic variability. Performing a next - generation sequencing panel, including the ANKRD11 gene for cases of developmental delay with/without short stature may be helpful to identify hitherto undiagnosed KBG syndrome patients.